Apakah Endorsement Selebriti, Pesta Diskon, dan Kesadaran Merek berpengaruh terhadap Keputusan Pembelian Online? : Studi Kasus: Shopee - Intan Isra’ Nur Laily Brilian; Rayhan Gunaningrat; Esti Dwi Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was conducted to evaluate the extent to which celebrity endorsements, discount parties, and brand awareness influence online purchasing decisions on the Shopee platform. A quantitative approach was adopted, with a survey conducted on 100 students who actively shop on Shopee. The sample was selected using purposive sampling. Data was compiled by distributing online questionnaires using Google Forms, then analyzed using the SEM-PLS approach through the SmartPLS 3 software. The findings showed that the three independent variables had a significant influence on online purchasing decisions, with discount events being the most influential factor. The findings emphasize the significance of digital marketing strategies that incorporate celebrity involvement, time-based promotions, and brand awareness to encourage consumers to shop online.